History Painting Crossing Borders, A Transnational History of Modern Art in Early Twentieth-Century China and Japan - Su, Stephanie, (Asian Studies E-Books Online, Collection 2025, 2025)
This book explores the transcultural relationship between China and Japan as it was negotiated through the practice of history painting from the 1890s to the 1940s. During this period, ancient China was reimagined to be an idealized cultural entity that accommodated divergent views on conceptualizing East Asian identities. Focusing on two pioneering artists in Japan and China, Nakamura Fusetsu (1866-1943) and Xu Beihong (1895-1953), this book highlights how historical connections across East Asia led to modern nations and artistic traditions. By comparing two artists through the lens of genre, this book has connected art practice and historiography in new ways.